Quantitative Proteomics Based on iTRAQ Reveal that Nitidine Chloride Induces Apoptosis by Activating JNK/c-Jun Signaling in Hepatocellular Carcinoma Cells - Chen, Shipeng; Liao, Yinan; Lv, Jinyan; Hou, Huaxin; Feng, Jie (Planta Medica, 2022)
The aim of the present study was to investigate the cytotoxic effects and underlying molecular mechanisms of nitidine chloride (NC) in hepatocellular carcinoma cells via quantitative proteomics. MTT assays were used to detect the inhibitory effects of NC in Bel-7402 liver cancer cells, and the number of apoptotic cells was measured by flow cytometry. Quantitative proteomics technology based on iTRAQ was used to discover differential expressed proteins after NC treatment, and bioinformatic techniques were further used to screen potential targets of NC. Molecular docking was applied to evaluate the docking activity of NC with possible upstream proteins, and their expression was detected at the mRNA and protein levels by quantitative reverse transcription PCR and western blotting. NC inhibited the proliferation of Bel-7402 cells after 24 h of treatment and stimulated apoptosis in vitro. The proteomics experiment showed that NC triggers mitochondrial damage in HCC cells and transcription factor AP-1 (c-Jun) may be a potential target of NC (fold change = 4.36 ± 0.23). Molecular docking results revealed the highest docking score of NC with c-Jun N-terminal kinase (JNK), one of the upstream proteins of c-Jun. Moreover, the mRNA and protein expression of c-Jun and JNK were significantly increased after NC treatment (p < 0.05). These findings indicate that NC significantly induced mitochondrial damage in HCC cells, and induced apoptosis by activating JNK/c-Jun signaling.
Keywords: Zanthoxylum nitidum; Rutaceae; nitidine chloride; apoptosis; hepatocellular carcinoma; quantitative proteomics